Big bang nucleosynthesis limit on N_nu - Lisi, E; Sarkar, S; Villante, F (1999)
Recently we presented a simple method for determining the correlated uncertainties of the light element abundances expected from big bang nucleosynthesis, which avoids the need for lengthy Monte Carlo simulations. We now extend this approach to consider departures from the Standard Model, in particular to constrain any new light degrees of freedom present in the thermal plasma during nucleosynthesis. Since the observational situation regarding the inferred primordial abundances has not yet stabilized, we present illustrative bounds on the equivalent number of neutrino species N_nu for various combinations of individual abundance determinations. Our 95% C.L. bounds on N_nu range between 2 and 4, and can easily be reevaluated using the technique provided when the abundances are known more accurately.